2013
DOI: 10.1038/jcbfm.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Brain Bioavailability of Human Intravenous Immunoglobulin and its Transport through the Murine Blood–Brain Barrier

Abstract: Intravenous immunoglobulin (IVIg) is currently evaluated in clinical trials for the treatment of various disorders of the central nervous system. To assess its capacity to reach central therapeutic targets, the brain bioavailability of IVIg must be determined. We thus quantified the passage of IVIg through the blood-brain barrier (BBB) of C57Bl/6 mice using complementary quantitative and qualitative methodologies. As determined by enzyme-linked immunosorbent assay, a small proportion of systemically injected I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 44 publications
12
125
0
Order By: Relevance
“…Since hIgG are large molecules, they do not cross the BBB, or only in very small amount (o 0.01% of injected dose). 24 As shown in Figures 4D and 4E, no difference in hIgG concentrations in the hippocampus and the cortex was found between APOE2 and APOE4 mice after three intraperitoneal injections of 30 mg hIgG 96, 24, and 1 hour(s) before killing. These data corroborate [ 14 C]-sucrose data and confirm that no major breakdown of BBB integrity occurred in APOE4 mice.…”
Section: Reduction Of Relative Vessel Density and Thinner Basementmentioning
confidence: 71%
See 1 more Smart Citation
“…Since hIgG are large molecules, they do not cross the BBB, or only in very small amount (o 0.01% of injected dose). 24 As shown in Figures 4D and 4E, no difference in hIgG concentrations in the hippocampus and the cortex was found between APOE2 and APOE4 mice after three intraperitoneal injections of 30 mg hIgG 96, 24, and 1 hour(s) before killing. These data corroborate [ 14 C]-sucrose data and confirm that no major breakdown of BBB integrity occurred in APOE4 mice.…”
Section: Reduction Of Relative Vessel Density and Thinner Basementmentioning
confidence: 71%
“…The concentration of hIgG in each tissue was determined by specific enzyme-linked immunosorbent assay using hIgG Fc-specific antibodies for capture and the corresponding horseradish peroxidaseconjugated antibodies for detection (Jackson ImmunoResearch Laboratories, West Grove, PA, USA). 24 Figure 2. Relative vessel density in the hippocampus was reduced in APOE4 mice.…”
Section: Assessment Of Blood-brain Barrier Permeability With Human Immentioning
confidence: 99%
“…It has previously been shown that human‐derived IVIG is compatible with mouse models and no significant differences between IVIG and mouse IgG treatment groups have been observed (St‐Amour et al . ; Sudduth et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the estimation of the brain concentration of a given receptor is practically impossible, only the antibodies against CGRP will be first considered. 23,30 When translated to CGRP biologics, this indicates that they are 300-fold less concentrated in the brain than in plasma, thereby suggesting that they act outside the BBB. This represents a key functional, protective parameter also in light of the constitutive defect in autoreactive B cell negative selection in humans, and ensuing risk of autoimmune humoral attacks against the brain.…”
mentioning
confidence: 99%